Reporting Management Strategy Through Bookkeeping, Inventory, Official and Operational Vehicles, Riau Islands Provincial Government of Indonesia: Identification of William Dunn's Evaluation Indicators - Rahmansyah Putra; Andi Muamar; N. Novita (Golden Ratio of Data in Summary, 2026)
The relationship between bookkeeping, inventory and reporting systems of official and operational vehicles studied would be discussed through adaptation of qualitative approach as tiered research design supported by six evaluation indicators based on William Dunn, including effectiveness, efficiency, adequacy, equity, responsiveness, certainty and availability whose relevance to existing phenomenons in Riau Islands Province Regional Finance and Asset Board as sole locus of research. Meanwhile, focus on the problem statement related to phenomena that would be revealed, specifically the positive significance of evaluating the regional property administration in the Riau Islands Provincial Government, with a particular emphasis on the administration of official vehicles and operational service vehicles by the Riau Islands Province Regional Finance and Asset Board. The achievement of research targets, based on the evaluation of the administration of regional assets in the Riau Islands Provincial Government, focuses on the administration of official vehicles and operational service vehicles, supported by qualitative methods, descriptive analysis, and discussion of field observations, segmented from the perspective of field research by Miles and Huberman. The findings of this qualitative descriptive research add value for the Regional Finance and Asset Board of Riau Islands Province, as the implementer of sustainable public administration policies, and for the scientific community, in the implementation of William Dunn's empirical basis.